2019
DOI: 10.1155/2019/3481397
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid-Conjugated Mesoporous Silica Nanoparticles Loaded with Dual Anticancer Agents for Chemophotodynamic Cancer Therapy

Abstract: Present cancer treatments using chemotherapy are limited owing to both significant side effects to normal cells and high recurrence rates. In this study, we demonstrated cancer cell-targeting nanoparticles that load multiple anticancer agents for both specific treatments to cancer and substantial therapeutic effects. For this purpose, hyaluronic acid (HA) was conjugated to mesoporous silica nanoparticles (MSNs) for specifically targeting cancer cells. Moreover, the prepared HA-MSNs exhibited high drug loading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The bright‐field image analysis further revealed that significant accumulation of AuraTherm inside the cell after 6 h and 24 h. At the same time, free HA pretreatment showed a decrease in the number of AuraTherm inside the cells with a maximum number outside of the cells. This suggests that HA pretreatment blocks the CD44 receptors on the cell's surface and, thus, competes with the receptor‐mediated endocytosis of AuraTherm (32).…”
Section: Resultsmentioning
confidence: 99%
“…The bright‐field image analysis further revealed that significant accumulation of AuraTherm inside the cell after 6 h and 24 h. At the same time, free HA pretreatment showed a decrease in the number of AuraTherm inside the cells with a maximum number outside of the cells. This suggests that HA pretreatment blocks the CD44 receptors on the cell's surface and, thus, competes with the receptor‐mediated endocytosis of AuraTherm (32).…”
Section: Resultsmentioning
confidence: 99%
“…242,243 HA-functionalized MSNPs incorporating doxorubicin (DOX) and a photosensitizer Chlorin e6 (Ce6) was used in photodynamic therapy (PDT) and chemotherapy to treat squamous cell carcinoma 7 (SCC7). 244 The nanoconjugate (DOX/Ce6/HA-MSNP) binds CD44 ligand, and the whole complex undergoes endocytosis to exhibit photoinduced toxicity by forming highly reactive singlet oxygen (SO) in SCC7 cells. In other related studies, (i) doxorubicin loaded on HA-MSNPs functionalized with polyethyleneimine (PEI) has been used for targeted delivery with increased endosomal escape efficiency and controlled drug release; 245 (ii) CD44-targeted HA nanoparticles were used to deliver siRNA into tumor cells; 246 and (iii) HA-PEI/HA-PEG-based nanoparticles were also used to target CD44 on ovarian cancer for delivery of MDR1 siRNA in vivo to enhance drug potency and overcome MDRI-related multidrug resistance.…”
Section: Glycosaminoglycan−polymer Conjugatesmentioning
confidence: 99%
“…HA-functionalized MSNPs incorporating doxorubicin (DOX) and a photosensitizer Chlorin e6 (Ce6) was used in photodynamic therapy (PDT) and chemotherapy to treat squamous cell carcinoma 7 (SCC7) . The nanoconjugate (DOX/Ce6/HA-MSNP) binds CD44 ligand, and the whole complex undergoes endocytosis to exhibit photoinduced toxicity by forming highly reactive singlet oxygen (SO) in SCC7 cells.…”
Section: Synthetic Glycoconjugatesmentioning
confidence: 99%
“…The HA-MSNs are absorbed at almost a three times higher rate than the free MSNs in squamous cell carcinoma 7 (SCC7) cells. To improve the anticancer effects of chemotherapy and photodynamic therapy (PDT), DOX and chlorine e6 (Ce6) are loaded in the HA-MSNs (DOX/Ce6/HA-MSNs) where the formulation demonstrates a higher cytotoxicity on the SCC7 than the free DOX, HA-MSNs-DOX, or Ce6 alone, suggesting significant therapeutic effects of chemo-PDT [ 142 ]. The HA-MSNs synthesized via a facile amidation reaction has been proposed as an efficient strategy to overcome the MSNs agglomeration problem in physiological fluids.…”
Section: Drug Loading Release and Cellular Uptakementioning
confidence: 99%